Cardiovascular disease predictors and adipose tissue macrophage polarization: Is there a link? - Kralova Lesna, Ivana; Petras, Marek; Cejkova, Sona; Kralova, Anna; Fronek, Jiri; Janousek, Libor; Thieme, Filip; Tyll, Tomas; Poledne, Rudolf (European journal of preventive cardiology, 2018)
Background The risk of cardiovascular disease is closely connected to adipose tissue inflammation. The links between cardiovascular risk predictors and pro and anti-inflammatory macrophages in human adipose tissue were analysed to gain an insight into the pathophysiology of cardiovascular disease. Design Subcutaneous and visceral adipose tissues were obtained from 79 subjects, 52 living kidney donors (during nephrectomy) and 27 patients with peripheral artery disease (during arterial tree reconstruction). Methods Macrophage subsets were isolated from adipose tissues and analysed by flow cytometry using CD14, CD16, CD36 and CD163 monoclonal antibodies. The mutually adjusted differences of phagocytic pro-inflammatory (CD14 + CD16 + CD36high), anti-inflammatory (CD14 + CD16-CD163+) and transitional subsets of macrophages were analysed in relation to cardiovascular predictors (sex, age, body mass index, smoking, hypercholesterolaemia, hypertension and statin treatment). Results Age, male sex and hypercholesterolaemia were closely positively associated with the phagocytic pro-inflammatory macrophage subset in visceral adipose tissues. Interestingly, the proportion of phagocytic pro-inflammatory macrophages was relevantly decreased by statin therapy. A strong positive association of body mass index to the phagocytic pro-inflammatory subset was found in subcutaneous adipose tissues only. A minor transitional subpopulation, CD14 + CD16 + CD36lowCD163+, increased with age in both adipose tissues. This transitional subpopulation was also negatively associated with obesity and hypercholesterolaemia in visceral adipose tissues. Conclusion An effect of cardiovascular risk predictors on adipose tissue macrophage subpopulations was revealed. Interestingly, while age, male sex and hypercholesterolaemia were connected with the pro-inflammatory macrophage subpopulation in visceral adipose tissues, body mass index had a prominent effect in subcutaneous adipose tissues only. A decreasing effect of statins on these pro-inflammatory macrophages was documented.
Keywords: Sex Factors; onemocnění periferních arterií; statiny; Humans; Case-Control Studies; index tělesné hmotnosti; lidé středního věku; Body Mass Index; Cardiovascular risk factors; studie případů a kontrol; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Intra-Abdominal Fat; Female; rizikové faktory; makrofágy; dospělí; inflammation; věkové faktory; Phenotype; lidé; Biomarkers; sexuální faktory; statins; adipose tissue; Adult; fagocytóza; Subcutaneous Fat; Peripheral Arterial Disease; biologické markery; ženské pohlaví; nitrobřišní tuk; Male; Middle Aged; fenotyp; prognóza; hypercholesterolemie; Hypercholesterolemia; Age Factors; Macrophages; Inflammation Mediators; mužské pohlaví; mediátory zánětu; Phagocytosis; Prognosis; macrophage; Risk Factors; podkožní tuk